An Efficient Preparation of a Terminal Arylacetylene - ZENGIN, GULAY (Asian Journal of Chemistry, 2010)
In the past synthetic routes to arylacetylenes via crosscoupling reactions of expensive monosubstituted acetylenes, such as trimethylsilylacetylene, using Pd (0) reagents have been the commonly used practice. Due to the high costs of such monosubstituted acetylenes these routes are usually limited to small-scale preparations. An alternative route for the introduction of a protected ethynyl moiety may be via the use of 2-hydroxypropan-2-yl by way of the inexpensive reagent 2-methyl-3-butyn-2-ol. Subsequent hydrolysis and deprotection can thus generate the terminal acetylene group. However, the seemingly attractive 2-methyl3-butyn-2-ol reagent was not so effective as deprotection via removal of 2-hydroxypropan-2-yl was more complicated than as first appeared. Thus the traditional method of using trimethylsilylacetylene was proved to be the more effective way of introducing a terminal arylacetylene group.